Phase-Shift Control for Enhancing Misalignment Tolerance in UCA-Based OAM-MIMO Systems - Norifumi Kamiya; Masahiro Kawai; Eisaku Sasaki (IEEE Access)
This paper presents a novel approach for achieving high-capacity transmission utilizing sub-terahertz (THz) radio orbital angular momentum (OAM) multiplexing, specifically in scenarios where the radio link is susceptible to antenna misalignment. We focus on a radio OAM multiplexing system incorporating uniform circular antenna arrays (UCAs) at both the transmitter and receiver. While it is established that UCA-based OAM multiplexing can significantly enhance transmission capacity, its performance is notably sensitive to antenna misalignment, leading to capacity degradation. To mitigate this issue, we propose a novel closed-loop OAM system featuring adaptive phase-shift control for transmission signals. We also introduce efficient methods for optimizing the phase shift. An experimental demonstration of the radio OAM system employing the proposed phase-shift control method is provided, showcasing its efficacy in compensating for the effects of misalignment.